Power control and energy efficiency strategies for D2D communications underlying cellular networks - Melo, Yuri Victor Lima de (2015)
In a world where people count on their smartphone, smartwatch, tablet and other devices to keep them connected wherever they go, they expect its application to run without problems, such as dropped calls, slow download and choppy videos. In this context, Device-to-Device (D2D) communication represents a promising technology, because it is a direct and low-power communication between devices close, allowing to offload the data transport network, increase spectral and power efficiency. From the subscriber point of view, D2D means to use applications without problem and increase battery life. However, in order to realize the potential gains of D2D communications, some key issues must be tackled, because D2D communications may increase the co-channel interference and compromise the link quality of cellular communications. This master’s thesis focuses on Radio Resource Management (RRM) techniques, especially Power Control (PC) schemes, to mitigate the co-channel interference for D2D communications underlaying a Long Term Evolution (LTE) network, aiming at the reduction of the intra- and inter- cell interference and at the improvement of energy efficiency. The main PC schemes (e.g. OLPC, CLPC and SDPC) and a hybrid scheme (CLSD) are calibrated and used in macro- or micro- multicell scenario, using different loads and imperfect Channel State Information (CSI). In addition, the impact of downtilt is analyzed, which is used to adjust the coverage radius of an Evolved Node B (eNB) and reduce co-channel interference by increasing cell isolation. The numerical results indicate that PC schemes and downtilt, duly calibrated, can provide gains to cellular and D2D communications. In other words, D2D technology can be used to further increase the spectral and energy efficiency if RRM algorithms are used suitably.